Development of web-based solar pv powered weather station - Muhammad Aiman, Umar (2012)
The weather station is an important component in achieving optimum plant monitoring and planning. The weather station will be able to measure changes in weather station parameter .In this project, the main objective is to provide real-time measurement weather station monitored system via website. This simple weather station will be powered by solar photovoltaic (PV). Solar PV will be used because it is environmental friendly. The weather station will show environmental parameters like temperature, humidity and rain gauge only. Then, the data will be updated every second in the website development. LabView is software that will be used for user interfacing and NI USB-6216 DAQ card is used to collect data from weather station parameter. This will give a low-cost solution for remote place because no longer need to go to the weather station to check the data that has been received from the weather station.